Opera at Columbia: A Shining Legacy - Griffel, Margaret Ross (Current Musicology, 2005)
Opera has always been central to my life. Listening to the Saturday afternoon broadcasts from the Metropolitan Opera was a ritual in my parents’ home, and we talked about our visits to the Met (albeit in the “nosebleed” seats) for weeks afterward. My love for opera was further nourished by my years at New York City’s High School of Music and Art, then some twenty blocks north of Columbia University, during which time Handel oratorios were semistaged at the school’s major concerts and Aaron Copland’s The Second Hurricane (1937) was revived at Carnegie Hall in a 1960 performance by M&A students conducted by Leonard Bernstein. In the 1960s, it was my good fortune to attend Barnard College and then do graduate studies in musicology at Columbia, where chances to hear contemporary as well as older operas abounded and opera composers such as Douglas Moore, Otto Luening, Henry Cowell, and Jack Beeson were members of the faculty. Sadly, such opportunities diminished in the following decades, breaking Columbia’s tradition of being a major source for the creation and performance of operas, which had reached its height in the 1940s and 1950s-the heyday of the Columbia Opera Workshop. After a brief history of the Workshop, the present article examines what it was like to be an opera -loving student at Columbia in the mid -1960s when Current Musicology was launched. Surrounded by the prominent composers mentioned above and other former participants of the Workshop who still taught courses in the Department of Music, including Willard Rhodes and Howard Shanet, we students had the chance to hear new and rarely performed works on campus or at nearby music conservatories and opera houses. In addition, this essay explores the contributions of Columbia graduates, particularly composers, to the world of opera. The article’s final two sections detail the operas given at various Columbia locations from 1941 to 2004. The first lists operas presented by the Music Department and the Workshop. It also includes those operas that were put on independently during the same period at venues such as McMillin Theatre (later renamed Miller Theatre), Barnard College’s Minor Latham Playhouse, and Brooks Hall, which featured Mozart operas in honor of his bicentennial year of 1956. The second section describes operas that were given at various Columbia locations after the Workshop closed.